Association between Metabolic Syndrome and Musculoskeletal Status: A Cross-Sectional Study of NHANES - Yue Shi; Shuhan Li; Xiaolong Xie; Yue Feng (International Journal of Endocrinology)
Objective. The metabolic effects of metabolic syndrome (MetS) on musculoskeletal metabolism are controversial. This study explored the effect of MetS on bone mineral density (BMD) and muscle quality index (MQI). Methods. Data from the NHANES database from 2011 to 2014 were extracted, and nonpregnant participants aged 45–59 years were included. The included data were first weighted by complex sampling, and then, the effect of MetS on BMD and MQI was analyzed using multifactorial linear regression. We then performed a stratified analysis by gender and BMI classification. Moreover, a mediation analysis of MetS on BMD was conducted, with MQI as a mediating variable. A propensity score matching analysis method with a complex sampling design was additionally performed to verify the stability of the results. Results. A total of 1943 participants were eventually included. After adjusting for covariates, the results of linear regression show that MetS is associated with elevated pelvic BMD (beta = 0.03; 95% CI = 0.01, 0.06; P=0.02) and reduced MQI, especially arm MQI (beta = −1.02; 95% CI = −1.27, −0.77; P<0.0001). MetS is more associated with BMD in women, MQI in normal or heavyweight, and BMD in lightweight, according to stratified analysis. MQI explains the indirect effect of MetS on BMD (beta = 0.007; 95% CI = 0.003, 0.010). Conclusion. This study provides evidence that MetS elevates BMD and reduces MQI, and further, that there is a mediating effect of MQI on elevated BMD.